TINDAKAN HUKUM DISKRESI DALAM KONSEP WELFARE STATE PERSPEKTIF HUKUM ADMINISTRASI NEGARA DAN HUKUM ISLAM - Aristoni, Aristoni (LP2M IAIN kUDUS, 2014)
DISCRETIONARY LEGAL ACTION (FREIESER- MESSEN) IN THE WELFARE STATE CONCEPT: PERSPECTIVE OF STATE ADMINISTRATION LE- GAL AND ISLAMIC LAW. Regulation of wisdom known as discretionary or ‘freiesermessen’ essentially is a legal act of government or supplies tool of state administration. This action carried out by the agency or the officials carrying out the government affairs to be able to act on their own initiative in solving social problems. This paper is an analysis of discretion or ‘freiesermessen’ as one of the means to move for official or administrative departments of the State to take action without having to be bound completely on legislation. As a result, in the ideal level, the government has the authority to make discretionary without being tied entirely to the law. But in practical terms, it does not mean that the government or officials of the State administration can act arbitrarily, but rather an attitude that must be accounted for. In other words, despite government intervention in the lives of citizens is indispensable in the conception of the welfare state, but also the accountability of each government action is indispensable in a State of law that upholds the values of truth and justice. keywords: Law act, Discretion, State administration legal, Islamic Law.Peraturan kebijaksanaan yang dikenal dengan istilah diskresi atau freiesermessen pada hakikatnya merupakan tindakan hukum pemerintah atau alat perlengakapan administrasi Negara. Tindakan ini dilakukan oleh badan atau pejabat yang melaksanakan urusan pemerintahan untuk dapat bertindak atas inisiatif sendiri dalam menyelesaikan persoalan-persoalan sosial. Tulisan ini merupakan analisis terhadap diskresi atau freiesermessen sebagai salah satu sarana yang memberikan ruang bergerak bagi pejabat atau badan-badan administrasi Negara untuk melakukan tindakan tanpa harus terikat sepenuhnya pada undang-undang. Hasilnya, pada tataran ideal, pemerintah memang diberikan kewenangan untuk membuat diskresi tanpa harus terikat sepenuhnya pada undang-undang. Namun pada tataran praktis, tidak berarti pemerintah atau pejabat administrasi Negara dapat bertindak semena-mena, melainkan sikap itu haruslah dipertanggungjawabkan. Dengan kata lain, meskipun campur tangan pemerintah dalam kehidupan warga Negara merupakan keniscayaan dalam konsepsi welfare state, tetapi pertanggungjawaban setiap tindakan pemerintah juga merupakan keniscayaan dalam Negara hukum yang menjunjung tinggi nilai-nilai kebenaran dan keadilan.kata kunci: Tindakan hukum, Diskresi, Hukum administrasi negara, hukum Islam.